Patrons of Enlightenment - Andrew, Edward, 1941- (Book collections on Project MUSE., 2006)
Patrons of Enlightenment emphasizes the dependency of thinkers upon patrons and compares the patron-client relationships in the French, English, and Scottish republics of letters.